Treinamento de carga progressiva para quadríceps associado a exercícios de propriocepção na prevenção de quedas em mulheres com osteoporose pós-menopausa: um ensaio clínico randomizado - Teixeira, Lucas Emmanuel Pedro de Paiva [UNIFESP] (2009)
OBJECTIVE: To evaluate the effect of a progressive muscular strength and proprioception training program on the muscle strength of the quadriceps, balance, quality of life and reduction in the risk of falls in postmenopausal women with osteoporosis. METHODS: One hundred sedentary postmenopausal women with osteoporosis, ages ranging from 55 to 75, were selected and randomized into two groups: the intervention group comprised of 50 patients who underwent a 18-week of progressive load training for the quadriceps muscle (50%, 60%, 70% up to 80% of 1- RM – one maximum repetition) and proprioception training associated to a drug treatment of osteoporosis and the control group that included 50 patients who only underwent a drug treatment of osteoporosis. The muscular strength, balance, functional mobility and quality of life were evaluated in the beginning and end of the research through the One Maximum Repetition Test (1-RM), Berg Balance Scale (BBS), Timed Up & Go Test (TU & GT) and SF-36. The number of falls was evaluated 6 months preceding the research and in the following six months. Results: Eighty-five patients concluded the research. The program promoted a significant difference among the groups for SF-36 in the eight sub-scales (p ≤ 0.0018), Timed Up & Go Test (p < 0.0001), 1-RM test (p < 0.0001), Berg Balance Scale (p < 0.0001) and also a decrease in the number of falls in the intervention group compared to control (IRR 0.263, 95% CI 0.10, 0.68). Conclusion: The association of progressive strength training for the quadriceps and the proprioceptive training is effective for the prevention of falls, increasing the muscle power, the static and dynamic balance and increasing the speed of the motor responses, therefore improving the performance of daily activities.